Exploring the implications of tutor negativity towards a synthetic agent in a learning-by-teaching environment - Rodrigo, Ma. Mercedes T.; Geli, Regina Ira Antonette M.; Ong, Aaron; Vitug, Gabriel Jose G.; Bringula, Rex; Basa, Roselle S.; Dela Cruz, Cecilio; Matsuda, Noboru (Philippine computing journal)
We examine the implications of negativity in free-form dialogue between student tutors and a synthetic agent in APLUS, a learning-by-teaching online learning environment for Algebra. We attempt to determine the whether the negativity of a student tutor's discourse...